Calcined Co-chelating, imine-crosslinking chitosan as the ORR catalyst of an anion exchange membrane fuel cell - Yen-Zen Wang; Ko-Shan Ho; Yu-Chang Huang; Yu-Wei Cheng; Chia-Long Miao; Pei-Ying Yeh (Carbon Trends)
Cobalt-chelating imine-crosslinked chitosan (Co-ICCA) is synthesized via Schiff base condensation of terephthalaldehyde and chitosan in the presence of cobalt chloride. Co-ICCA transforms into Co, N-co-doped carbon cathode catalysts (Co-N-Cs) upon calcination. The successful synthesis is confirmed using Fourier Transform Infrared Spectroscopy. The porous morphologies of the calcined Co-ICCA are characterized by transmission electron microscopy, high-resolution transmission electron microscopy, and field-emission scanning electron microscopy. The Co-N-Cs exhibit a high specific surface area (433 m²/g) and porosity, as analyzed by a BET analyzer. X-ray diffraction patterns reveal sharp graphite diffraction peaks and feature peaks of Co-crystal with an FCC lattice when the calcination temperature exceeds 800 °C, indicating high crystallinity.Meanwhile, Raman spectra show a higher G-band intensity compared to the D-band. The performance of Co-N-Cs as cathode catalysts, particularly in the oxygen reduction reaction, is evaluated through current-voltage and linear sweep voltammetry curves and compared to commercial Pt/C catalysts. Single-cell using the Co-N-C catalyst as the cathode reaches a high maximum power density of 221 mW cm-2, close to the 285 mW cm-² achieved with Pt/C as the cathode catalyst.